1959
DOI: 10.1103/physrev.116.131
|View full text |Cite
|
Sign up to set email alerts
|

Angular Distributions of Deuterons fromLi7(p, d)Li6

Abstract: Angular distributions of deuterons from Li 7 (^,^)Li 6 reactions induced by 17.5-Mev protons on a natural lithium target have been observed at angles less than 50 degrees in the laboratory system. Deuteron groups leaving Li 6 in its ground state and in states at 2.19 and 3.57 Mev were studied, and the branching ratios were compared with intermediate coupling shell theory. Pure or nearly pure L-S coupling was found to be adequate to explain the observed ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1961
1961
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Thus, we have some independent knowledge of the location of the lenses in both cases of observed microlensing events towards the SMC, and they both are due to self-lensing within the SMC. Towards the LMC, there is only one binary event, MACHO-LMC-9, for which we have independent knowledge of the location of the lens (Bennett et al 1996) where the lens is inferred to be within the LMC. Thus, out of all the events observed so far towards the LMC and the SMC, there are a total of 3 events for which we have some independent knowledge of the location of the lenses: 2 towards the SMC as stated above, and one towards the LMC (MACHO-LMC-9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have some independent knowledge of the location of the lenses in both cases of observed microlensing events towards the SMC, and they both are due to self-lensing within the SMC. Towards the LMC, there is only one binary event, MACHO-LMC-9, for which we have independent knowledge of the location of the lens (Bennett et al 1996) where the lens is inferred to be within the LMC. Thus, out of all the events observed so far towards the LMC and the SMC, there are a total of 3 events for which we have some independent knowledge of the location of the lenses: 2 towards the SMC as stated above, and one towards the LMC (MACHO-LMC-9).…”
Section: Discussionmentioning
confidence: 99%
“…This is due, in part, to SoDOPHOT's error flags, which allow the removal of suspect data points (Alcock et al 1999), but the scatter in DOPHOT photometry is often increased by the user's choice of point-spread function (PSF) fitting parameters. Contrary to expectations, allowing the PSF fit box size to scale with the seeing generally causes increased photometric scatter (Bennett et al 1993). The photometric errors reported by SoDOPHOT are modified by adding of 1.4% and 1.0% in quadrature to the MACHO and MPS data, respectively, to account for normalization and flat-fielding errors.…”
Section: The Data Setmentioning
confidence: 99%
“…The MACHO and MPS data were reduced with slightly different versions of the SoDOPHOT photometry code (Bennett et al 1993;Alcock et al 1999). SoDOPHOT is quite similar to the DOPHOT photometry code (Schechter, Mateo, & Saha 1993) that it was derived from, but SoDO-PHOT photometry generally exhibits smaller photometric scatter than DOPHOT photometry.…”
Section: The Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Circumprimary systems have been examined by Lee et al (2008), but notably Poleski et al (2014) and Gould et al (2014) have recently found examples of such planets. 4 To date, only one microlensing event has been claimed to be caused by a circumbinary planet, MACHO-97-BLG-41L (Bennett et al 1999), but this was later shown to be caused by binary stars with orbital motion (Albrow et al 2000;Jung et al 2013;Han et al 2016). There have been no other microlensing circumbinary planet detections published, and relatively little theoretical work on microlensing by circumbinary planets, with only a brief paper by Han (2008b) addressing them directly.…”
Section: Introductionmentioning
confidence: 99%